2019
DOI: 10.1124/dmd.119.086504
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided In Vitro to In Vivo Pharmacokinetic Optimization of Propargyl-Linked Antifolates

Abstract: Pharmacokinetic/pharmacodynamic properties are strongly correlated with the in vivo efficacy of antibiotics. Propargyl-linked antifolates, a novel class of antibiotics, demonstrate potent antibacterial activity against both Gram-positive and Gram-negative pathogenic bacteria, including multidrug-resistant Staphylococcus aureus. Here, we report our efforts to optimize the pharmacokinetic profile of this class to best match the established pharmacodynamic properties. High-resolution crystal structures were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The other approach which has also gained popularity in the recent years focuses on targeting DHFRs, being useful for both Gram-positive and Gram-negative bacteria, including TMP-resistant species too. Propargyl-linked antifolates consists of a highly conserved diaminopyrimidine ring linked through an acetylenic group to a biaryl system which allows the tunability of the compounds as shown in Figure 10 [119,120]. The success of these drugs on the resistant DHFR enzymes is based on their shared action mechanism, where the diaminopyrimidine ring binds a conserved acidic residue of the enzyme allowing the rest of the molecule to penetrate into the active site [119].…”
Section: Current Experimental Compounds and Future Trends On Antifmentioning
confidence: 99%
See 1 more Smart Citation
“…The other approach which has also gained popularity in the recent years focuses on targeting DHFRs, being useful for both Gram-positive and Gram-negative bacteria, including TMP-resistant species too. Propargyl-linked antifolates consists of a highly conserved diaminopyrimidine ring linked through an acetylenic group to a biaryl system which allows the tunability of the compounds as shown in Figure 10 [119,120]. The success of these drugs on the resistant DHFR enzymes is based on their shared action mechanism, where the diaminopyrimidine ring binds a conserved acidic residue of the enzyme allowing the rest of the molecule to penetrate into the active site [119].…”
Section: Current Experimental Compounds and Future Trends On Antifmentioning
confidence: 99%
“…Propargyl-linked antifolates consists of a highly conserved diaminopyrimidine ring linked through an acetylenic group to a biaryl system which allows the tunability of the compounds as shown in Figure 10 [119,120]. The success of these drugs on the resistant DHFR enzymes is based on their shared action mechanism, where the diaminopyrimidine ring binds a conserved acidic residue of the enzyme allowing the rest of the molecule to penetrate into the active site [119]. These novel drugs have achieved inhibitory potencies in the nanomolar scale and therefore are promising candidates for antibiotic purposes [8,115].…”
Section: Current Experimental Compounds and Future Trends On Antifmentioning
confidence: 99%
“…Attempts to cocrystallize or soak 4 also failed to return any structures containing density indicative of 4 binding. The Sa DHFR structure was previously determined with NADPH, TMP, and other folate-mimicking derivatives. The inclusion of 4 at saturating concentrations with Sa DHFR did not yield crystals under previously determined conditions, and broad screens for new conditions did not successfully produce visible protein crystals. Using the previous conditions (10 mg/mL SaDHFR), we grew crystals with NADPH (1.1 mM) and TMP (saturating) in addition to 4 at saturating conditions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The antibacterial effect of time-dependent drugs could not be enhanced by increasing concentrations, compared to concentrationdependent drugs. 31 For time-dependent antibacterial agents, treatment outcomes could be improved by extending the treatment course. These results showed that compounds 14 and 15 had a bacteriostatic effect at high concentrations and displayed very promising antimicrobial activity against MRSA.…”
Section: 2mentioning
confidence: 99%